Transnationalization of science and technology policies in Central America. A network analysis 1955-2020 - Ronny Viales-Hurtado; Ronald Sáenz-Leandro; Marco Garita-Mondragón (Íconos)
The present article argues that the dissemination of ideas about the relationship between science, technology and society in Central America, is framed by transnationalization processes, which, in turn are driven by regional international organizations, think tanks and non-governmental organizations (NGO’s). This conclusion is reached after examining the official documents and the transnational networks generated by the flow of these ideas in Latin America. In the heyday of CEPAL-inspired developmentalism in the region, the Central American Institute for Industrial Research and Technology (ICAITI) became a key player in the development of Latin American thought on science, technology and society. ICAITI, with the help of foreign aid programs sponsored by western powers, was instrumental in establishing the scientific development policies that became dominant in Central America. Due to both internal and external factors, the “Cepalian” development model reached its limits around the decade of the 80’s and this led to the demise of the institute. However, between the 80’s and the 90’s the liberalization of the Central American economies and the restructuring of the science, technology and society institutions in the region provided other transnational actors with the opportunity to influence the agenda of scientific development. The new approach involves the supremacy of a neo-liberal and economistic perspective that is still dominant in our times.